Using multi-agency, multi-professional collaboration to reduce serious violence and organized crime - Rachel A. Staniforth; Una Jennings; Jamie Henderson; Simon Mitchell (Journal of Community Safety and Well-Being, 2019)
Serious violence and organized crime have been rising both nationally and in Sheffield, contributing significantly to increasing knife and gun crime, which results in threats to community safety and well-being. A multi-agency project with stakeholders across all levels of command and co- located operational staff was established to undertake collaborative activity that would protect the public by pursuing offenders as well as preparing for and preventing serious violence and organized crime: Fortify. Using a 4P approach, Fortify worked across professional and organizational boundaries to disrupt serious violence and organized crime. Relationships between partners have improved substantially through increased communication and understanding of the different roles, perspectives, and levers of each partner. A recent Home Office locality review applauded our partnership. Intelligence sharing has improved, leading to increased disruptive activity, including increased seizure of money, drugs, and firearms, as well as more arrests and safeguarding referrals. The number of mapped Organized Crime Groups (OCGs) operating across the city has reduced from 19 to 12. Processes and procedures have improved, reducing duplication and holding of information in silos. Community groups are more engaged, allowing us to address serious violence and organized crime in partnership. We propose to undertake action research with the involvement of all partners to provide more robust evaluation of our initial findings. We have found that collaboration between Police and Partners increases collective responsibility and facilitates success in tackling serious violence and organized crime.